Synthesis, characterization and application of Fe-zeolite: A review - Zhang, Jie; Tang, Xiaolong; Yi, Honghong; Yu, Qingjun; Zhang, Yuanyuan; Wei, Jinghui; Yuan, Yuting (Applied catalysis. A, General, 2022)
Fe-zeolites are widely applied in petrochemical, fine chemical, environmental protection, and other catalytic fields because of the zeolitic properties as well as the redox properties endowed by the introduction of Fe species. After being introduced into the zeolitic framework, the poor properties of traditional aluminosilicate zeolites, i.e., lack of active sites, low catalytic activity, poor anti-coking performance, etc., could be effectively improved. The state of Fe species in zeolite, which significantly affects the properties (stability, acidity, redox properties, etc.) of Fe-zeolite, was determined by both the introduction methods/conditions and the properties (porosity / acidity, etc.) of zeolite. From this point of view, a clear understanding of the structure-activity relationship of Fe-zeolite is an important prerequisite for designing functional materials as necessary. Therefore, in this review, recent developments on the synthesis, properties as well as the application of Fe-based zeolites were briefly summarized. In detail, the factors affecting the recognition of types as well as the distribution of Fe species in Fe-zeolites and the effects of the introduction of Fe on the physicochemical properties & catalytic performance of zeolites are systematically clarified. Then, the applications of Fe-zeolite in chemical industry and environmental engineering were reviewed and outlooked. This review is expected to provide theoretical reference for the structural design and application of Fe-based zeolites in the future. [Display omitted] •The types, existing forms and distribution of iron incorporated into zeolites were summarized.•Identification signals of various iron species in Fe-zeolites were summarized systemically.•Key factors affecting iron species distributed in zeolites were discussed.•The incorporation of iron endows zeolite good hydrophobicity and catalytic oxidation performance.•Recent development about Fe-zeolites applied in industry were presented.